2008
DOI: 10.1002/ss.284
|View full text |Cite
|
Sign up to set email alerts
|

Student perspectives on multiracial identity

Abstract: This chapter describes the perspectives and experiences of multiracial college students and offers recommendations for institutions of higher education to better support college students who identify as multiracial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Regardless of their gender, students were more ambitious than employees. These results are in agreement with studies in which boys' and girls' university students show similar levels of ambitions (King, 2008). An explanation could relate to the malleability of gender stereotypes (Diekman & Eagly, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regardless of their gender, students were more ambitious than employees. These results are in agreement with studies in which boys' and girls' university students show similar levels of ambitions (King, 2008). An explanation could relate to the malleability of gender stereotypes (Diekman & Eagly, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Referring to stereotypes, we could discuss the differing level of ambition to leadership positions women and men may have. In fact, studies with young boys and girls (Blackhurst & Richard, 2018), or with university students (King, 2008), show that they have similar levels of ambition or even that female students express higher career aspirations than male counterparts (Watts et al, 2015). Furthermore, results show that university graduates in general expect to attain future upward social mobility (Shane & Heckhausen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This will lead to an increase in the number of biracial or multiracial students in institutions of higher education. King [18] found that going to college actually precipitated a racial identity crisis among multiracial people, as they were unsure where they fit in. Currently, institutions of higher education provide services to students from different races, as historically these populations have attended college at lower rates than Caucasian students, and are less likely to complete their degree program.…”
Section: Discussionmentioning
confidence: 99%
“…Multiracial individuals may develop identity differently from monoracial people. Researchers have found that going to college actually precipitated a racial identity crisis among multiracial people, as they were unsure where they fit in the larger student population, often divided by race [11,18]. Demographic forms can also pose a problem for multiracial students in higher education because, while individual colleges may have demographic forms that allow students to identify multiracially, the data is collapsed and reported in only monoracial categories for some institutional or national statistical reporting [14].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Such assumptions contradict contemporary data which indicate that students entering higher education increasingly have multiracial identities. Even though the multiracial student population continues to grow in colleges and universities, many multiracial students continue to face racial microaggressions, feelings of exclusion, and a persistent struggle to define their racial identity within their campus cultures (Kellogg & Liddell, 2012;King, Renn, & Shang, 2008;Harris, 2017;Renn, 2000).…”
Section: Introductionmentioning
confidence: 99%